2015
DOI: 10.3402/gha.v8.28209
|View full text |Cite
|
Sign up to set email alerts
|

A partial validation of the WHOQOL-OLD in a sample of older people in South Africa

Abstract: BackgroundThis paper describes the psychometric properties of the WHOQOL-OLD, an add-on module to the World Health Organization's Quality of Life measure for older people in a South African sample. The WHOQOL-OLD module was further condensed into three short versions which contain the best items of the original module. The psychometric properties associated with the three short versions of the WHOQOL-OLD are also described.MethodData were collected from Afrikaans-speaking older people (n=176) residing in long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 30 publications
4
23
0
Order By: Relevance
“…The identified 6-factor solution that best fitted the study data was congruent with the reported priori factor structure of the original scale [11] and in the validation study of the Dutch version of the WHOQOL-OLD [38], however; the hypothesized model structure of the instrument in other studies [12,13,15,16,19,32] were incompatible.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The identified 6-factor solution that best fitted the study data was congruent with the reported priori factor structure of the original scale [11] and in the validation study of the Dutch version of the WHOQOL-OLD [38], however; the hypothesized model structure of the instrument in other studies [12,13,15,16,19,32] were incompatible.…”
Section: Discussionsupporting
confidence: 62%
“…In the development of the original WHOQOL-OLD module, the interviewees' scores were considered to exhibit floor/ceiling effects on the basis of the percentage of the respondents with maximum or minimum total scores that exceeds 20% [11]. The WHOQOL-OLD-P by this categorization, connoted no substantial floor and ceiling effects, indicative of its discriminant ability identical to the findings of the other WHOQOL-OLD crosscultural validation studies [14,17,19,32,33]. However; in a number of previous studies a tendency towards ceiling effect [11,34,35] in measurement of well-being, life satisfaction and QOL was suggested due to probability of rampant positivity bias [8].…”
Section: Discussionmentioning
confidence: 95%
“…The dependent variable used in the analysis was subjective wellbeing (SWB), calibrated through the World Health Organization 12-item quality of life brief (WHOQOL-Bref) questionnaire, shown to be a valid measure of SWB among the elderly [70][71][72]. The analysis specifically examined evaluative wellbeing.…”
Section: Methodsmentioning
confidence: 99%
“…The outcome of HRQoL was assessed using the WHOQOL-Old [42]. WHOQOL-Old is a well-developed instrument with adequate reliability and validity, and has been widely used to assess HRQoL in many countries [43]. The WHOQOL-Old contains 24 items distributed into six subscales: sensory abilities; autonomy; past, present, and future activities; social participation; death and dying; and intimacy.…”
Section: Health-related Quality Of Life (Hrqol)mentioning
confidence: 99%